STEM VIRTUAL LAB : AN ALTERNATIVE PRACTICAL MEDIA TO ENHANCE STUDENT’S SCIENTIFIC LITERACY - Ismail, I.; Permanasari, A.; Setiawan, W. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2016)
This research aimed to develop a STEM-based virtual lab as an alternative media in improving scientific literacy of junior high school students on the theme of water pollution. Development is done by using 4D methods: Define, Design, Develop, and Disseminate. After the implementation was done, it’s effectiveness in increasing scientific literacy was examined using one group pretest-posttest design. At the define stage problems from PISA 2012, KDs, and STEM characteristics were analyzed. Design of flowcharts, storyboards, and user interface were done on design phase. Phases of develop includes the creation of virtual labs and validation by media expert and a science teacher. Phases of disseminate this research is to implement limited to two classes of junior high school students. The results from media expert validation and science teachers validates that STEM-based virtual labs that have been developed shows very decent used in the feasibility study by percentage according to media expert at 86.24% and 82.71% according to science teacher. The results show that the implementation of the STEM-based virtual lab that has been developed can improve scientific literacy of students with a large increase (N-gain) in the class 7B of 0.46 which falls in to medium category and class 7D of 0.29 with medium category.